Respiratory and Other Hazard Characteristics of Substances in Cleaning Products Used in Healthcare Centres in England and Wales - Sewon Lee; Andrew Povey; Martin Seed; Martie Van Tongeren (Elsevier, 2024)
Occupational use of cleaning products can cause asthma in healthcare workers but the cleaning agents responsible are not yet known. This study aimed to identify respiratory and other hazards in cleaning products on the National Health Service (NHS) supply chain online catalogue and used in the NHS. Information on cleaning products, their composition, and H-statements that identified hazard characteristics of chemical substances in them was obtained from chemical safety data sheets (SDSs). Furthermore, a quantitative structure-activity relationship model and a published asthmagen list were used to identify potential additional respiratory hazards. 473 cleaning products and 229 substances were identified. SDSs reported only 4 respiratory sensitizers but an additional 51 were suggested by the other 2 methods. In contrast, 25 respiratory irritants were identified using SDSs and only one from the asthmagen list. This comprehensive overview of cleaning agents' hazards has potential use in future risk assessment and epidemiological studies.